STRATEGIC MEASURES TO INCREASE THE COMPETITIVENESS OF THE AGRICULTURAL SECTOR OF UKRAINE IN THE INTERNATIONAL MARKET - PAVLOVA, Galina; ABRAMOVYCH, Inna; BALZAN, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The publication is aimed at researching the state of competitiveness of domestic products of the agrarian sector of production on the international market and, on this basis, substantiating directions for increasing its competitiveness at various levels of influence with the selection of strategic decisions and the necessary conditions for their adoption. The importance of the selected research topic is also confirmed by the opinion of scientists regarding the consequences of an unsatisfactory level of competitiveness of domestic agricultural products on the situation of the domestic market. In the process of revealing the topic, attention was paid to the issues of the essence of the competitiveness of agricultural enterprises, the main basic premise - soil fertility, as well as the state and trends of the export of agricultural products on the international market. It was determined that such agricultural products as vegetables, fruits, berries and melons remain almost inactive in international trade, although their cultivation in Ukraine is quite successful. The prospect of such a direction is the trend of the population transitioning to a healthy diet and the statements of doctors about the benefits of year-round consumption of berries and vegetables, which is a stimulating factor in the growth of demand both in our country and in Europe. The expediency of intensifying the innovative activity of agricultural enterprises of Ukraine in order to increase their competitive positions on the basis of high product quality and the possibility of painlessly adjusting the sales price on both domestic and foreign markets has been proven. Directions for increasing the competitiveness of the agricultural sector of Ukraine on the international market are proposed, with the selection of strategic measures at the state level of management of agro-industrial production and the level of agricultural commodity producers. The steady growth of the world market of agricultural products and products of their processing in recent decades determines promising directions for the development of agricultural enterprises and creates conditions for increasing the export of products. The main factors in the formation of competitive advantages are favorable natural, climatic and geographical conditions for the production of products, the availability of conditions for ensuring high quality and environmental safety, convenient logistical transport location, etc.